THE IMPACT OF AFFINITY, CONVENIENCE, AND SOCIAL MEDIA MARKETING IN INFLUENCING INTEREST IN USING SHARIA E-BANKING - Achmad Saifulloh Fatah; Saifudin (IAIN Langsa, 2022)
This study aims to determine the effect of affinity, convenience, and social media marketing on interest in using sharia e-banking with trust as a moderating variable (a case study of millennial society in Semarang Regency). The sample used in this study was 100 respondents with a simple random sampling technique. The data collection was carried out by giving questionnaires to the millennial community of Semarang Regency. The analysis used is the research instrument test, statistical test, classical assumption test, and MRA (moderated regression analysis). Furthermore, the data is processed using the analysis software, namely SPSS version 22. From the test results obtained: 1) affinity has no effect on interest in using sharia e-banking, 2) ease has a significant positive effect on interest in using sharia e-banking, 3) social media marketing has a significant positive effect on interest in using sharia e-banking, 4) trust is unable to moderate the effect of affinity on interest in using sharia e-banking, 5) trust can moderate the effect of convenience on interest in using sharia e-banking, 6) trust can moderate the influence of social media marketing on interest in using sharia e-banking. Islamic banking institutions can use the results of this study to increase public trust in the institution.